2015
DOI: 10.1016/j.jinf.2014.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory trial of ombitasvir and ABT-450/r with or without ribavirin for HCV genotype 1, 2, and 3 infection

Abstract: In this study, ombitasvir and ABT-450/r ± RBV regimens were generally well-tolerated. Sustained virologic response was achieved in most patients with HCV genotype 1 or 2 infection, but low SVR rates were observed in HCV genotype 3-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
32
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 35 publications
4
32
0
Order By: Relevance
“…Among substitutions at the highly conserved A156, A156G/S generally resulted in minor fitness impairment, whereas A156T/V resulted in strong fitness impairment. This is in line with previous studies, suggesting relatively high fitness of genotype 1a, 2a, and 6 A156S versus A156T/V variants in vitro and in vivo (13,(52)(53)(54), and the fact that A156G/S variants were frequently found in genotype 1 and, more recently, also in genotype 2 and 3 PI-treated patients (9,10,14,16,21,26). Changes at position 168, harboring a highly conserved glutamine in genotype 3 and aspartic acid in other genotypes, did not result in major fitness impairment for most genotypes, as was previously suggested for genotype 1 (52).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Among substitutions at the highly conserved A156, A156G/S generally resulted in minor fitness impairment, whereas A156T/V resulted in strong fitness impairment. This is in line with previous studies, suggesting relatively high fitness of genotype 1a, 2a, and 6 A156S versus A156T/V variants in vitro and in vivo (13,(52)(53)(54), and the fact that A156G/S variants were frequently found in genotype 1 and, more recently, also in genotype 2 and 3 PI-treated patients (9,10,14,16,21,26). Changes at position 168, harboring a highly conserved glutamine in genotype 3 and aspartic acid in other genotypes, did not result in major fitness impairment for most genotypes, as was previously suggested for genotype 1 (52).…”
Section: Discussionsupporting
confidence: 93%
“…In line with our findings, a previous study suggested relatively high fitness of genotype 1a R155K/T versus R155G/Q variants in vitro (52). In addition, the fact that R155K was frequently found in genotype 1 and, more recently, also in genotype 2, 3, and 5 PI-treated patients indicates a relatively high fitness (9,10,14,16,18,21,26,53). Among substitutions at the highly conserved A156, A156G/S generally resulted in minor fitness impairment, whereas A156T/V resulted in strong fitness impairment.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…3) (28) are indicated by NA (not applicable). genotypes 2 to 6 (4,8), recent clinical and in vitro studies on selected genotypes and substitutions suggested that these patterns might be found across genotypes (50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65). Certain substitutions were preferentially acquired by specific recombinants, depending on the genetic barrier to resistance, as evidenced by the fact that the substitutions identified were encoded by a single nucleotide change.…”
Section: Discussionmentioning
confidence: 99%